THE PRINCIPLE OF OPERATION OF MECHANICAL WASTEWATER TREATMENT - Murodov, D.M; Jamolova, N.; Qurbonova, D.T (Educational Research in Universal Sciences, 2022)
Wastewater treatment is a set of measures aimed at removing pollutants contained in wastewater. Special equipment is installed to perform the task in question. Often, the process of wastewater treatment is divided into 4 main stages: biological, mechanical, physico-chemical, disinfection. In this article we will consider the features of the mechanical method of wastewater treatment in more detail.